Developing an Inclusive education teaching aptitude test: Pilot testing and item selection - Mistry, Hemendra S. (Voices of Teachers and Teacher Educators, 2023)
Pilot testing refers to pre-testing of a particular research instrument. Pilot study is a crucial element of a good study design; it fulfils a range of important functions and can provide valuable insights for other researchers. This paper reports the pilot testing process of draft inclusive education teaching aptitude test (IETAT), principally focusing on the trial version of actual test administration along with item analysis in terms to determine difficulty values and internal consistency indexes of test items. Data were collected from 38 pre-service teachers of a teacher education institution. Result indicated that the pilot testing helped in removing the weak items with ambiguity and deficiency, standardisation of test instruction and time limit, and developing the final version of IETAT. This paper highlights the importance of pilot testing in terms of improving the test item validity, adds to the body of knowledge on pilot studies, and contributes to the development of test development.